Cardiovascular Disease Risk Factor Burden During the Menopause Transition and Late Midlife Subclinical Vascular Disease: Does Race/Ethnicity Matter? - Barinas‐Mitchell, Emma (J Am Heart Assoc, 2020)
BACKGROUND: The extent to which cardiovascular disease (CVD) risk factors across the menopause explain racial/ethnic differences in subclinical vascular disease in late midlife women is not well documented and was explored in a multi‐ethnic cohort. METHODS AND RESULTS: Participants (n=1357; mean age 60 years) free of clinical CVD from the Study of Women's Health Across the Nation had common carotid artery intima‐media thickness, interadventitial diameter, and carotid plaque presence assessed by ultrasonography on average 13.7 years after baseline visit. Early to late midlife time‐averaged cumulative burden of traditional CVD risk factors calculated using serial measures from baseline to the ultrasound visit were generally less favorable in black and Hispanic women compared with white and Chinese women, including education and smoking status and time‐averaged cumulative blood pressure, high‐density lipoprotein cholesterol, and fasting insulin. Independent of these risk factors, BMI, and medications, common carotid artery intima‐media thickness was thicker in black women, interadventitial diameter was wider in Chinese women, yet plaque presence was lower in black and Hispanic women compared with white women. CVD risk factor associations with subclinical vascular measures did not vary by race/ethnicity except for high‐density lipoprotein cholesterol on common carotid artery intima‐media thickness; an inverse association between high‐density lipoprotein cholesterol and common carotid artery intima‐media thickness was observed in Chinese and Hispanic but not in white or black women. CONCLUSIONS: Race/ethnicity did not particularly moderate the association between traditional CVD risk factors measured across the menopause transition and late midlife subclinical vascular disease. Unmeasured socioeconomic, cultural, and nontraditional biological risk factors likely play a role in racial/ethnic differences in vascular health and merit further exploration.